Salicylic acid improves the antioxidant ability against arsenic-induced oxidative stress in sunflower (Helianthus annuus) seedling. (2nd October 2017) - Saidi, Issam; Yousfi, Nasreddine; Borgi, Mohamed Ali
ABSTRACT: The present study investigated the potential role of external salicylic acid (SA) in alleviating Arsenic (As) toxicity in sunflower leaves. The exposure of plants to 10 µM As inhibited biomass production and intensively increased the accumulation of As in both roots and leaves. The levels of some important parameters associated with oxidative stress, namely lipid peroxidation, electrolyte leakage, and hydrogen peroxide (H2 O2 ) production were increased. SA application alleviated the negative effect of As on growth and led to decrease in oxidative injuries. Furthermore, SA application led to higher activity of catalase, ascorbate peroxidase, and glutathione peroxidase, and concomitantly decreased superoxide dismutase and guaiacol peroxidase activities. As important antioxidants, ascorbate and glutathione contents in sunflower leaves exposed to As were significantly decreased by SA treatment. These results reveal that SA is more effective in alleviating As toxicity at higher concentrations than that at lower concentrations.